2019
DOI: 10.3390/ma12030457
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Cracking Behavior of Powder Metallurgy and Ingot Metallurgy Ti-5Al-5Mo-5V-3Cr Alloys during Hot Deformation

Abstract: The hot workability of metallic materials is significantly dependent on its ability to form plastic without cracking and fracturing. In this work, the cracking behavior of powder metallurgy (PM) Ti-5Al-5Mo-5V-3Cr (Ti-5553) alloy, consolidated from powder mixture, at a deformation temperature range of 600 °C–850 °C and strain rate of 0.1 s−1–10 s−1, was investigated through isothermal compression tests. The cracking behavior of the as-cast ingot metallurgy (IM) Ti-5553 alloy, at a deformation temperature of 700… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…High-intensity and symmetric diffraction peaks corresponding to the β phase were present at 2θ values (deg) of 39.45 (172,771 counts, 0.52 deg fwhm), 58.54 (10,855 counts, 1.47 deg), and 72.02 (6248 counts, 2.19 deg fwhm). , The weakly intense, symmetric peak at a 2θ value of 35.45 deg (1632 counts, 0.49 deg fwhm) and asymmetric peak at a 2θ value of 85.40 deg (3254 counts, 1.33 deg fwhm) are associated with α and α″ phases, respectively. The peak assignments are based on comparison of diffraction pattern data for this alloy. ,,,, The high intensity of the peak at a 2θ of 39.45 deg indicated that the alloy has a considerable amount of β phase. This is expected because this alloy consists of relatively high atomic levels of the β phase stabilizing elements Mo, V, and Cr.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…High-intensity and symmetric diffraction peaks corresponding to the β phase were present at 2θ values (deg) of 39.45 (172,771 counts, 0.52 deg fwhm), 58.54 (10,855 counts, 1.47 deg), and 72.02 (6248 counts, 2.19 deg fwhm). , The weakly intense, symmetric peak at a 2θ value of 35.45 deg (1632 counts, 0.49 deg fwhm) and asymmetric peak at a 2θ value of 85.40 deg (3254 counts, 1.33 deg fwhm) are associated with α and α″ phases, respectively. The peak assignments are based on comparison of diffraction pattern data for this alloy. ,,,, The high intensity of the peak at a 2θ of 39.45 deg indicated that the alloy has a considerable amount of β phase. This is expected because this alloy consists of relatively high atomic levels of the β phase stabilizing elements Mo, V, and Cr.…”
Section: Resultsmentioning
confidence: 99%
“…Higher-magnification SEM micrographs (secondary and backscattered electron images) for an abraded, polished, and etched specimen (XZ plane) are presented in Figure 6C,D The peak assignments are based on comparison of diffraction pattern data for this alloy. 2,6,47,52,63 The high intensity of the peak at a 2θ of 39.45 deg indicated that the alloy has a considerable amount of β phase. This is expected because this alloy consists of relatively high atomic levels of the β phase stabilizing elements Mo, V, and Cr.…”
Section: Density Measurementsmentioning
confidence: 99%
See 1 more Smart Citation